Area-Selective ZnO Thin Film Deposition on Variable Microgap Electrodes and Their Impact on UV Sensing. (4th June 2013) - Humayun, Q.; Kashif, M.; Hashim, U.
Abstract : ZnO thin films were deposited on patterned gold electrodes using the sol-gel spin coating technique. Conventional photolithography process was used to obtain the variable microgaps of 30 and 43  μ m in butterfly topology by using zero-gap chrome mask. The structural, morphological, and electrical properties of the deposited thin films were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and Keithley SourceMeter, respectively. The current-voltage ( I - V ) characterization was performed to investigate the effect of UV light on the fabricated devices. The ZnO fabricated sensors showed a photo to dark current ( I ph / I d ) ratios of 6.26 for 30  μ m and 5.28 for 43  μ m gap electrodes spacing, respectively. Dynamic responses of both fabricated sensors were observed till 1V with good reproducibility. At the applied voltage of 1 V, the response time was observed to be 4.817 s and 3.704 s while the recovery time was observed to be 0.3738 s and 0.2891 s for 30 and 43  μ m gaps, respectively. The signal detection at low operating voltages suggested that the fabricated sensors could be used for miniaturized devices with low power consumption.